Study on coupling characteristics and parameter optimization of thermoelectric generation via radiative cooling (RC-TE) system. (25th June 2023) - Lv, Song; Li, Zhuoyi; Zhang, Bolong; Ren, Juwen; Ji, Yishuang; Yang, Jiahao
Highlights: A three-dimensional finite element model of a RC-TE system is built. The results show that when the radiative area ratio is about 33.18, the maximum voltage of RC-TE can be 234.5 mV. Compared with ideal condition, the output under semi-ideal and convection condition is reduced by 66.62% and 86.63%, respectively. These findings will have an important positive impact on the optimal design and practical application of RC-TE. Abstract: Combining radiative cooling (RC) with Thermoelectric (TE) generators to realize passive power generation has been considered to be one of the potential green energy sources, which can achieve the effect of low temperature power generation without the input of external energy. Although some theoretical and experiments have proved that TE can obtain energy from radiative cooling, the realized power density is very low. That is because the limited temperature difference between the two ends of the TE devices caused by the low energy density of the RC significantly reduces the output performance. In addition, the calculation model in the existing research is often simplified, and the influence of complex structure on the energy absorption of the system cannot be accurately considered. Therefore, this paper presents a detailed three-dimensional study on the effect of the structure and configuration of the RC-TE system, and the influence of environmental factors on the performance of the RC-TE. Here, we built a three-dimensional finite element model of a RC-TE system in COMSOL. The three different heat transfer boundaries model were established on the surface of RC to numerically study the performance of the RC-TE devices. The influence of RC-TE structure and surrounding environmental parameters on the performance of RC-TE is comprehensively explored, including radiative area ratio, wind speed, ambient temperature, and triethylene glycol structure parameters β. The results show that when the radiative area ratio is about 33.18, the maximum voltage of RC-TE can be 234.5 mV under ideal conditions. However, compared with the ideal condition, the output performance under the semi-ideal condition and the convection condition is reduced by 66.62% and 86.63%, respectively. As ambient temperature rises from 0 ° C to 30 ° C, the maximum voltage is ideal condition about 210.63 mV, while convection condition has greater increase about 49.79 %. As the TE structure β increases, the output performance is significantly weakened and the rate of reduction gets bigger. The purpose of this study is to analyze, verify, simulate and optimize the prototype radiation cooled thermoelectric generator (RC-TE) model to improve efficiency. These findings will have an important positive impact on the optimal design and practical application of RC-TE.